PENGARUH PUASA INTERMITEN TERHADAP KESEHATAN HORMONAL DAN REPRODUKSI WANITA: TINJAUAN LITERATUR - Fadhilah Witris Salamy, Nanda; Sophia Matin, Nur (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: Intermittent fasting (IF) has gained popularity as a nutritional approach for weight management and metabolic improvement. However, its effects on women's hormonal and reproductive health remain controversial, as the female endocrine system is highly sensitive to energy intake fluctuations and circadian rhythm shifts. Objective: This review aims to evaluate recent literature on the impact of IF on reproductive hormone balance, menstrual cycle, fertility, and long-term risks in women. Method: The method employed was a systematic review of 10 scientific articles retrieved from PubMed, ScienceDirect, and Nature databases published between 2018 and 2025. Results: Findings indicate that IF may offer hormonal benefits, especially for women with polycystic ovary syndrome (PCOS), through improved insulin sensitivity, menstrual regularity, and ovulation. However, IF also poses potential risks such as amenorrhea, anovulation, and delayed sexual maturation, particularly when applied without considering circadian alignment and nutritional status. Furthermore, fasting schedules that conflict with women’s biological rhythms may disrupt endocrine function and reproductive performance. Conclusion: In conclusion, while IF presents promising benefits, its implementation in women must be individualized and approached with caution, considering age, hormonal profile, and lifestyle. These findings are expected to guide health practice in providing evidence-based nutritional education and reproductive health interventions for women of reproductive age.